Artificial intelligence service recovery: The role of empathic response in hospitality customers' continuous usage intention. (January 2022) - Lv, Xingyang; Yang, Yufan; Qin, Dazhi; Cao, Xingping; Xu, Hong
Abstract: Artificial intelligence (AI) service failures are inevitable in hospitality companies; thus, how AI service recovery retains customers is an issue that cannot be ignored. This article focuses on AI service recovery, abandoning the traditional "intelligence quotient" thinking and exploring the recovery effect of empathy response from the perspective of emotional intelligence. Using four experimental scenarios, the results indicate that, in service recovery, a high-empathy AI response can increase customers' continuous usage intention, and psychological distance and trust are sequential mediators in this process. Compared with mono-sensory stimulus interactions (text only), a high-empathy response that adopts multisensory stimulus interactions (text and voice) could strengthen the recovery effect of empathy responses. This paper extends the field of AI service research from a focus on time and phase to the continuing use of AI after service failure. It also moves beyond the traditional intelligence quotient improvement thinking and reveals the importance of using AI emotional intelligence to activate customer emotional response in AI service recovery. Finally, it provides a useful tool for resolving AI service failure problems autonomously in the service process, which is of great value to research and development and hospitality operators in the promotion and application of AI services. Highlights: Artificial intelligence must perform service recovery independently. Activating customer emotional response is important. Empathic response is effective in artificial intelligence service recovery. Psychological distance and trust are the continuous intermediary mechanism. Multisensory interaction modality enhanced the effect of empathic response.